2007
DOI: 10.1111/j.1460-9568.2007.05594.x
|View full text |Cite
|
Sign up to set email alerts
|

No improvement by amphetamine on learned non‐use, attempts, success or movement in skilled reaching by the rat after motor cortex stroke

Abstract: Amphetamine (AMPH) has been proposed as a treatment for post-stroke motor deficits when coupled with symptom-relevant physical rehabilitation. Whereas a number of experimental studies report improvements in endpoint measures of skilled reaching for food by rats, there has been no assessment of whether beneficial effects extend to overcoming learned non-use of the limb in the acute post-stroke period or to the qualitative deficits in movement in the chronic post-stroke period. In addition to evaluating the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Clinical studies tend to select patients most in need of therapy, which are those with larger injuries. (Alaverdashvili et al, 2007) made small lesions similar to those of Moroz and Kolb but administered the same dose (1 mg/kg) orally rather than subcutaneously. They found no beneficial effect of the drug.…”
Section: Harnassing Plasticity For Neurorehabilitationmentioning
confidence: 97%
“…Clinical studies tend to select patients most in need of therapy, which are those with larger injuries. (Alaverdashvili et al, 2007) made small lesions similar to those of Moroz and Kolb but administered the same dose (1 mg/kg) orally rather than subcutaneously. They found no beneficial effect of the drug.…”
Section: Harnassing Plasticity For Neurorehabilitationmentioning
confidence: 97%
“…Some authors have even stated that using just a few (often only one) behavioral measures may lead to biased estimates of behavior and that a better assessment of behavior comes from using a “battery” of species-typical and learned behaviors [105]. The use of simple “end point” measures also limits the interpretation of whether a motor behavior has returned [134, 136, 142]. Further, the fractionation of more complex behaviors (e.g., reaching) enables researchers to determine what is possible with regard to recovery and whether animals are using compensatory behaviors [134, 143].…”
Section: Behavioral Effects Of Recovery/compensationmentioning
confidence: 99%
“…Eight out of 13 preclinical trials in animals demonstrated beneficial effects of coupling of d-amphetamine administration with physical and cognitive training [17,19,[21][22][23][24][25][26] in improvement of motor and cognitive recovery after brain injury, whereas four studies [16,18,20,27] could not detect an improved recovery. Papadopoulos et al [17] even reported a full recovery to baseline performances, but only with the coupled therapy of amphetamine and physical training.…”
Section: Brain Injury and Amphetaminesmentioning
confidence: 95%